Dinâmica organizacional, teoria dos recursos da firma e inovação: um estudo de caso dos processos de aprendizagem em uma empresa inovadora - Moda, Luciane de Campo (2006)
Authors such as BARNEY (1991, 2001), HAMEL and PRAHALAD (1995) argue that the Resources of the Firm can be an important source of competitive advantage. Despite the fact that these sources are represented by several resources (a strategy, a product, a competitive differential), several studies say that the capacity of the Firm in promoting organizational learning, are fundamental to obtain sustained competitive advantage. The theories show that organizational core competencies, source of innovation, need to be mapped and improved continuously, in an organizational learning process. Therefore, a People Management Model that promotes double looping learning and innovation will be a source of sustainable competitive advantage. This study intends to investigate how the trinomial: Innovation, Organizational Learning and People Management Model, happen in a company that identifies itself as an innovative company.